Role of heterogenous microstructure and deformation behavior in achieving superior strength-ductility synergy in zinc fabricated via laser powder bed fusion - Zhi Dong; Changjun Han; Yanzhe Zhao; Jinmiao Huang; Chenrong Ling; Gaoling Hu; Yunhui Wang; Di Wang; Changhui Song; Yongqiang Yang (International Journal of Extreme Manufacturing, 2024)
Zinc (Zn) is considered a promising biodegradable metal for implant applications due to its appropriate degradability and favorable osteogenesis properties. In this work, laser powder bed fusion (LPBF) additive manufacturing was employed to fabricate pure Zn with a heterogeneous microstructure and exceptional strength-ductility synergy. An optimized processing window of LPBF was established for printing Zn samples with relative densities greater than 99% using a laser power range of 80 ∼ 90 W and a scanning speed of 900 mm s ^−1 . The Zn sample printed with a power of 80 W at a speed of 900 mm s ^−1 exhibited a hierarchical heterogeneous microstructure consisting of millimeter-scale molten pool boundaries, micrometer-scale bimodal grains, and nanometer-scale pre-existing dislocations, due to rapid cooling rates and significant thermal gradients formed in the molten pools. The printed sample exhibited the highest ductility of ∼12.1% among all reported LPBF-printed pure Zn to date with appreciable ultimate tensile strength (∼128.7 MPa). Such superior strength-ductility synergy can be attributed to the presence of multiple deformation mechanisms that are primarily governed by heterogeneous deformation-induced hardening resulting from the alternative arrangement of bimodal Zn grains with pre-existing dislocations. Additionally, continuous strain hardening was facilitated through the interactions between deformation twins, grains and dislocations as strain accumulated, further contributing to the superior strength-ductility synergy. These findings provide valuable insights into the deformation behavior and mechanisms underlying exceptional mechanical properties of LPBF-printed Zn and its alloys for implant applications.